2017
DOI: 10.1177/0956797616688118
|View full text |Cite
|
Sign up to set email alerts
|

Do Young Drivers Become Safer After Being Involved in a Collision?

Abstract: As drivers age, their risk of being involved in a car collision decreases. The present study investigated if this trend is due, in part, to some risky drivers having a collision early in their driving lives and subsequently reducing their risky driving after that negative experience. Accelerometers and video cameras were installed in the vehicles of 16- to 17-year-old drivers (N = 254), allowing coders to measure the number of g-force events (i.e., events in which a threshold acceleration level was exceeded) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…As a result, underestimating risk is associated with a higher propensity to engage in risky behaviour [ 40 , 41 ]. Some studies have demonstrated that the majority of young drivers tend to underestimate risk and engage in risky driving even after being involved in a car crash [ 42 ]. Although these drivers were observed to be more cautious while driving during the first two months after the collision, this cautiousness was no longer observed after the third month.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, underestimating risk is associated with a higher propensity to engage in risky behaviour [ 40 , 41 ]. Some studies have demonstrated that the majority of young drivers tend to underestimate risk and engage in risky driving even after being involved in a car crash [ 42 ]. Although these drivers were observed to be more cautious while driving during the first two months after the collision, this cautiousness was no longer observed after the third month.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate this more formally, we used the SHRP2 naturalistic driving data set that includes some 245 young drivers . We calculated the rates of KRD before and after each crash and found that the rates declined for at least 2 months, whereas the rates among those who did not crash remained stable, consistent with an effect of learning from crash experience …”
Section: Statistical Methods and The Naturalistic Teenage Driving Studymentioning
confidence: 76%
“…18 We calculated the rates of KRD before and after each crash and found that the rates declined for at least 2 months, whereas the rates among those who did not crash remained stable, consistent with an effect of learning from crash experience. 40 As with CNC, the variability in KRD among novice teenage drivers could only be examined in longitudinal research using naturalistic driving methods; hence, it was not known before the NTDS. Using latent class models of KRD over the 18-month period, Simons-Morton et al 33 found 2 trajectory classes best characterized the overtime distribution, with substantial variability in within groups.…”
Section: Ntds Methods Researchmentioning
confidence: 99%
“…As noted KRD declines when feedback is provided to both young drivers and their parents [8,22]. Using SHRP-2 data on 17-18-year-old drivers [58], it was reported that KRD declined after a crash (police-reportable severity), suggesting that teens moderated their driving behavior in response to crashing. The research suggests that KRD is a unique risk factor for young drivers, given the dramatically higher rate of KRD among novices than adult drivers in all studies where it has been measured.…”
Section: Evidencementioning
confidence: 99%
“…There is considerable individual variability in KRD rates, but the characteristics of the variability in this behavior are not well studied. (3) Could the findings of O'Brien and colleagues [58] that reported declines in KRD after a crash be replicated with other samples of young drivers and with older drivers? (4) Would reductions in KRD rates improve crash outcomes?…”
Section: Research Gapmentioning
confidence: 99%